Passage of Pseudomonas aeruginosa in compromised mice. - Cox, C D (1979)
There was no appreciable increase in the virulence of Pseudomonas aeruginosa PAO-1 after six passes through infections in mice. When strain PAO-1 was passed through mice compromised with iron and methotrexate, the virulence of the passed bacteria increased for normal as well as compromised mice. Bacteria harvested from intraperitoneal passage in compromised mice were more virulent than bacteria harvested from intrathoracic passage. These bacteria expressed 50% lethal dose values distinctive of the respective bacterial isolate when injected intraperitoneally, intrathoracically, or intravenously. Differences between bacteria from intraperitoneal and intrathoracic passage were apparently due to differences in the selective pressures in the two sites of infection, because the intrathoracically passed bacteria assumed the virulence characteristics of the intraperitoneally passed bacteria after intraperitoneal passage in compromised mice.